Childhood family risks and mental health of older adults in China: The moderating effect of age - Xinzhu, Wang (Frontiers in Psychology, 2023)
Introduction: childhood family risks (CFRs) have been believed to have long-armed effects on people’s mental health. However, whether or not age can alleviate the long-armed effects is still unclear. Aim: this study aimed to explore the relationship between CFRs and mental health for older adult Chinese, and whether age could moderate this relationship. Methods: This cross-sectional, survey-based study used data from the Chinese General Social Survey conducted in 2015, and a sample of 4237 subjects were entered into final analysis. Mental health was measured by two items including both negative and positive emotions. Step-by-step regression procedure and moderation analysis technique were used. Results: for older adults in China, CFRs could negatively predict their mental health (β=-0.046, t=-2.690, p < .01), and age could positively predict their mental health (β=0.115, t=7.157, p<.01), and age could significantly moderate the relationship between CFRs and mental health (β=0.277, t=2.172, p<.05). When age increases, the effects of CFRs on mental health decreases gradually, and when age is one standard deviation above the mean, CFRs could not predict mental health significantly ( bsimple= -0. 01，t = -. 077, p＞0. 05). Conclusions: This study showed that CFRs can have negative effects on mental health for older adults in China, and age could alleviates the effects significantly. Therefore, it is essential to take preventive measurements in advance to protect people’s mental health, and to teach older adults to use emotion-regulation techniques to offset the negative effects of CFRs on their mental health.